Literature Review: The Effect of the Flipped Classroom on Student Chemistry Learning - Saputra, Bayu; Solihatin, Etin; Muslim, Suyitno; Raini, Yeni; Silfianah, Ifah (Jurnal Pendidikan dan Pembelajaran Kimia, 2023)
The research delves into the impact of the flipped classroom model on student learning outcomes in chemistry education, utilizing a literature review methodology and systematically analyzing nine scopus-indexed articles. The flipped classroom, characterized by independent pre-class learning and in-class interactive activities, consistently demonstrates positive effects on academic performance, engagement, and motivation in chemistry education. The synthesis encompasses diverse methodologies, educational levels, and outcomes, highlighting the model's adaptability across different contexts. Critiques, including uncertainties about contributing factors, prompt recommendations for future research, such as exploring blended learning models and integrating Artificial Intelligence for personalized learning experiences. In conclusion, while acknowledging variations and critiques, the literature underscores the flipped classroom's effectiveness and advocates for ongoing research to refine its implementation in diverse educational settings.Keywords: Flipped classroom,  pendidikan kimia, teknologi pendidikan, tinjauan literatur DOI: 10.23960/jppk.v12.i3.23.16